2019
DOI: 10.1111/pbi.13214
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in MIR396e and MIR396f increase grain size and modulate shoot architecture in rice

Abstract: SummaryGrain size and plant architecture are critical factors determining crop productivity. Here, we performed gene editing of the MIR396 gene family in rice and found that MIR396e and MIR396f are two important regulators of grain size and plant architecture. mir396ef mutations can increase grain yield by increasing grain size. In addition, mir396ef mutations resulted in an altered plant architecture, with lengthened leaves but shortened internodes, especially the uppermost internode. Our research suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…In the flanking region of SZ3, we identified a microRNA, miRNA396, and gene Rc03G006134. MiRNA396 is implicated in the regulation of seed size and yield in rice [ 50 , 51 ] and Rc03G006134 encodes an orthologue of the transposase-like DAYSLEEPER gene in Arabidopsis and is essential for normal plant growth, especially cotyledon development [ 52 ]. The gene Rc05G010958 near the flanking region of the GWAS signal for SA and SSW (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the flanking region of SZ3, we identified a microRNA, miRNA396, and gene Rc03G006134. MiRNA396 is implicated in the regulation of seed size and yield in rice [ 50 , 51 ] and Rc03G006134 encodes an orthologue of the transposase-like DAYSLEEPER gene in Arabidopsis and is essential for normal plant growth, especially cotyledon development [ 52 ]. The gene Rc05G010958 near the flanking region of the GWAS signal for SA and SSW (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, some DEMs such as miR156, miR160, miR166, miR167, miR168, miR395, miR396, miR397, miR398, miR399, and miR408 were also found to be differentially expressed during seed development in many seed plants [ 4 , 18 , 19 , 21 30 ]. In rice, miR156, miR160, miR167, miR396, miR397, miR389, and miR408 have been functionally verified to regulate the rice seed development [ 31 38 , 40 ]. These suggested that these known miRNAs were the key and conserved miRNAs in different plant seed development regulation and could also be used as candidate miRNAs for Tartary buckwheat seed development.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR396a was suppressed to approximately 50% in the tomato plants that overexpressed lncRNA44664 (OE-lnc44664), and the target genes of Solyc10g083510.1 were significant increased ( Figure 6B). miR396 was found to be associated with GRFs (growth-regulating factors) [24]. The expression of miR156d was suppressed to approximately 50% in the tomato plants that overexpressed lncRNA48734 (OE-lnc48734), and the target genes of Solyc05g012040.2 were significantly increased ( Figure 6C).…”
Section: Function Verification Of Lncrnasmentioning
confidence: 99%